Extender composition for cryopreservation of Tenualosa ilisha spermatozoa with specific reference to inhibition of motility - Lal, Kuldeep K; Punia, Peyush; Ponniah, A G (Indian Journal of Fisheries, 2011)
The behaviour of spermatozoa of Tenualosa ilisha in response to commonly usedextenders proved to be different from other fishes studied. The extenders usedfor cryopreservation of spermatozoa of various cyprinid and salmonid fishes werefound to be unsuitable for T. ilisha as they activate the sperm on dilution. Theinhibtion point of hilsa sperm motility was assessed by exposing the milt samplesto different concenterations of potassium chloride, ranging from 500 mg to 2500mg in an extender containing NaCl 5500mg, NaHCOj 20mg, CaClj 20mg, MgSO^10 mg per 100ml with DMSO @ 10%. At 500 mg/100 ml concentration, spermatozoawere found inactive in the extended milt and exhibited good motility uponactivation with filtered river water. The milt samples were frozen with sevenextenders composed of base extender containing KCl 1500mg/100ml with additives,mannitol, BSA, 2% yolk and glucose with 10% DMSO as cryoprotectant. Post thawmotility after 212 days of cryofreezing indicated that the extender with 2% eggyolk was superior to others.